HUBUNGAN KARAKTERISTIK AKSEPTOR KB SUKU MADURA DENGAN PEMILIHAN JENIS KONTRASEPSI DI PUSKESMAS OMBEN KABUPATEN SAMPANG - Nanda Rizaldi (Jurnal Sehat Mandiri, 2021)
The amount of people in Indonesia always increase over and over each year so the government implement a program called KB or Family Planning which aims to control the birth rate of the country. In implementing KB program, there are many debatable pro-cons in people, one of them is Madurese people who assume that one of the contraceptives are considered inadequate to be used from a religious and cultural perspective. This study aims to find out the relationship between a Madurese family planning acceptor and the choice of contraception. The research method is analytic observational with Cross Sectional Study. The method of sampling is probability type, used the simple random sampling. This study used questionnaire to collect the data and chi-square test to analyse the data. The result of the study showed that the respondents who choose short-term contraception type is 95 people and the long-term contraception is 15 people. The result of the data analysis showed that there is a relationship of age (0,043), number of children (0,006), economical status (0,005), and socio-cultural (0,002) in choosing the contraception type. Meanwhile, the education (0,923) has no relation in the choose of contraception type.. It is expected that the prospective family planning acceptors can increase their knowledge of KB (Family Planning) and for the health service workers can increase the health promotion of KB so people can broaden their knowledge of KB.